2017
DOI: 10.1111/are.13386
|View full text |Cite
|
Sign up to set email alerts
|

Practical diets with essential oils of plants activate the complement system and alter the intestinal morphology of Nile tilapia

Abstract: The effect of the essential oils (EOs) of peppermint, Mentha piperita L., and tea tree, Melaleuca alternifolia (Maiden & Betche) Cheel, on the haematological, biochemical, and immunological parameters and intestinal morphology of Nile tilapia, Oreochromis niloticus L., was evaluated. Fish (58.09 ± 5.87 g) were fed 100 mg/kg and 250 mg/kg of each EO and sampled on days 7, 14, 30 and 60 after starting supplementation. The haematological and biochemical parameters were not altered by the supplementation of EOs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This could be related to the efficient nutrients utilization following the adequate regulation of the intestinal microbiota as evidenced in the current study. The EOs usage also may positively affect the features of gut morphology which enhance absorption and assimilation of nutrients (Valladão et al, 2017). Likewise, in another study, the addition of a commercial EOs product to rainbow trout diet modulated intestinal microbial communities (Giannenas et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This could be related to the efficient nutrients utilization following the adequate regulation of the intestinal microbiota as evidenced in the current study. The EOs usage also may positively affect the features of gut morphology which enhance absorption and assimilation of nutrients (Valladão et al, 2017). Likewise, in another study, the addition of a commercial EOs product to rainbow trout diet modulated intestinal microbial communities (Giannenas et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…The EOs usage also may positively affect the features of gut morphology which enhance absorption and assimilation of nutrients (Valladão et al, 2017). The EOs usage also may positively affect the features of gut morphology which enhance absorption and assimilation of nutrients (Valladão et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The zootechnical indexes of tilapia did not differ significantly between treatments (p > 0.05), and the final weight was consistent with the slaughter weight of this species when farmed in net cages. Recent studies have been carried out to evaluate the effects of diet on the hematological, immunological, and histological parameters or the gut microbiota of Nile tilapia [5,8,[35][36][37][38][39][40][41], which have contributed to our understanding of the effects of dietary constituents on different physiological aspects of this species. However, no study to date has evaluated these variables in an integrated manner and/or in real farming situations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that EO from some plants can be used to enhance immunity in fish as well as killing of certain bacteria and parasites of fish (i.e. Acar, Kesbiç, Yılmaz, Gültepe, & Türker, ; Brum et al, ; Brum et al, ; Ngugi, Oyoo‐Okoth, & Muchiri, ; Sutili et al, ; Sutili, Murari, et al, ; Sutili, Velasquez, et al, ; Valladão et al, ; Valladão, Gallani, Kotzent, Assane, & Pilarski, ; Valladão et al, ). However, the usage of EO or their isolated compounds as dietary supplements in fish is still limited in scope and application.…”
Section: Introductionmentioning
confidence: 99%